The Efforts to Improve the Skills of Finding Mandate in Poetry Through Multiple Choice Test Techniques in the High Classes - Muliza, Suci; Khairunisa; Indriyani, Dwi (Berpusi Publishing, 2023)
This research is based on the difficulties encounteredstudents' experience in writing poetry.This research aims to improve capabilitiesa student at SDN 053978 Tanjung IbusThis is done to provide motivation to students in learning to write poetry and provide a real learning experience that writing poetry using the acrostic technique can help students learn more actively, creatively andpleasant.Class 5 research subjects were 25 students consisting of 13 male students and 12 female students.The research was carried out using classroom action procedures (PTK). The data collection technique uses obsequential techniquesrvation and test. Research result found that in the initial or pre conditions The cycle of students' poetry writing abilities does not yet meet the minimum completeness criteria..